Ketokohan Tok Ku Paloh dan Pengaruhnya Terhadap Gerakan Penentangan Penjajah British di Pantai Timur: Tok Ku Paloh and his Influence on Anti British Colonial Movement in the Malaya East Coast - Azizi, Muhammad Zakwan; Mohd Azhar, Muhammad Hazim; Samat, Mohd Hafizie (Online Journal of Research in Islamic Studies, 2019)
The arrival of the Western colonial power to the Malay world is not just a matter of wealth and splendor, but they carry a hidden agenda to spread Christianity. Recognizing that fact, the Muslim community, especially in Malaya, rose against the colonial power. The emergence of ulama, among them like Tok Ku Paloh, had its own influence on the colonial opposition movement in the East Coast. Therefore, Tok Ku Paloh's characteristic research is based on this research based on his leadership in order to mobilize the spirit of struggle in society and leaders. In other words, this study proves that the fight against British colonialism in the East Coast was actually a major boost in parallel with the call of the Ottoman Caliphate to fight against the colonial invaders. Thus, the contributions of the ulama in the field of da'wah to foster the spirit of jihad is an important factor in the rise of the struggle of leaders and communities in the East Coast of Malaya.